2004
DOI: 10.1080/15287390490486833
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine-Disrupting Activity in Carbendazim-Induced Reproductive and Developmental Toxicity in Rats

Abstract: This study was designed to investigate the endocrine-disrupting activity of carbendazim-induced reproductive and developmental toxicity in Sprague-Dawley rats treated orally with the fungicide. Cotreatment of male rats with 675 mg/kg carbendazim and 50 or 100 mg/kg flutamide, an androgen receptor antagonist, once daily for 28 d blocked decrease of testis weight induced by treatment with carbendazim alone. The cotreatment prevented losses of spermatozoa and cell morphology and decrease of sperm concentration in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(28 citation statements)
references
References 37 publications
2
23
0
3
Order By: Relevance
“…Carbendazim works by inhibiting the development of fungi probably by interfering with spindle formation at mitosis. It is known to cause endocrine disrupting effects in vertebrates (Lu et al, 2004) and it has been found to affect the steroid synthesis pathway operating at the level of gene transcription through a microtubule-interfering mechanism (Morinaga et al, 2004). It also resulted a potent aneuploidogen (affecting the number of chromosomes) when applied to human lymphocytes even at low exposures (Bentley et al, 2000).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Carbendazim works by inhibiting the development of fungi probably by interfering with spindle formation at mitosis. It is known to cause endocrine disrupting effects in vertebrates (Lu et al, 2004) and it has been found to affect the steroid synthesis pathway operating at the level of gene transcription through a microtubule-interfering mechanism (Morinaga et al, 2004). It also resulted a potent aneuploidogen (affecting the number of chromosomes) when applied to human lymphocytes even at low exposures (Bentley et al, 2000).…”
Section: Discussionmentioning
confidence: 98%
“…The aim of the present work was to evaluate if carbendazim, known to be an endocrine disruptor in vertebrates (Lu et al, 2004), has sublethal effects on the demographic characteristics of Moina micrura, the dominant cladoceran (Vicente & Miracle, 1992, Miracle's 30-year observations) in rice fields and other aquatic ecosystems in the Albufera Natural Park in summer, when this chemical is applied. Likewise, this work has a worldwide interest since this species, besides living in temperate ecosystems, is also abundant in the tropics and carbendazim has been extensively used as a fungicide in tropical agriculture and its effects on tropical freshwater zooplankton have been considered, such as studies of whole communities in mesocosms (Daam et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Selmanoglu et al (2001) found that 300-600 mg/kg of carbendazim per day would affect liver and kidney tissues of rats and result in some adverse effects on haematological and biochemical parameters. Lu et al (2004) and Zhou et al (2004) reported on the endocrinedisrupting activity of carbendazim and suggest more attention should be paid to the effects on reproduction and ecotoxicology. A low dose of carbendazim is capable of inducing reproductive toxicity through increasing oxidative stress, but is transient and reversible upon withdrawal of treatment (Rajeswary et al, 2007).…”
Section: Introductionmentioning
confidence: 96%
“…There was evidence of adverse effects of carbendazim on various aspects of male reproduction in hamsters, mice, rats, and humans. These effects include decreased mean testes weight, caput sperm numbers, mean seminiferous tubular diameter (Carter et al, 1987), total sperm count, motility, increased incidence of sperm abnormalities (Akbarsha et al, 2001; Lu et al, 2004), and disruption of microtubule formation (Nakai et al, 2002). The main target of carbendazim is the spermatocytes (Kadalmani et al, 2002).…”
Section: Introductionmentioning
confidence: 99%